2022
DOI: 10.1155/2022/4156312
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Donepezil Hydrochloride plus Olanzapine for Senile Dementia and Its Effect on the Recovery of Cognitive Function

Abstract: Objective. To investigate the efficacy of donepezil hydrochloride plus olanzapine for senile dementia and its effect on the recovery of cognitive function. Methods. A total of 60 patients with senile dementia admitted to our hospital from April 2020 to July 2021 were recruited and assigned to receive either olanzapine alone (observation group) or donepezil hydrochloride plus olanzapine (experimental group) via the random number table method, with 30 patients in each group. Results. The combined therapy resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Aricept combined with olanzapine can significantly promote patients recover from the low cognitive function with dementia. Compared with olanzapine alone, the rate of side effects is similar, but the safety is controllable [18].…”
Section: The Effectiveness and Safety Of Ariceptmentioning
confidence: 99%
“…Aricept combined with olanzapine can significantly promote patients recover from the low cognitive function with dementia. Compared with olanzapine alone, the rate of side effects is similar, but the safety is controllable [18].…”
Section: The Effectiveness and Safety Of Ariceptmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%